Cardiac dysrhythmias among coronavirus-19 recovered symptomatic patients. (3rd October 2022) - Shamia, D; Tsaban, G; Baham, L; Raviv, Y; Haim, M
Abstract: Background: The coronavirus (COVID-19) pandemic, which affected millions of people worldwide, is associated with a chronic fatigue sequela, also known as long-COVID. While various adverse effects of COVID-19 on the cardiovascular system were reported, the prolonged sequela of COVID-19 on heart rhythm remains unknown. Aim: To describe the prevalence of cardiac dysrhythmias among patients who presented with Long Covid following recovery from COVID-19 infection. Methods: We conducted a prospective study among 87 patients who suffered from Long Covid syndrome following recovery from COVID-19 and were treated in the COVID-19 recovery clinic between December 2020 and June 2021. All patients were referred for transthoracic echocardiography (TTE) and 24-hour Holter examination. Results: The mean age was 52+13 years, and 52 (59.8%) patients were females. Seventy-nine (90.8%) of the patients had normal sinus rhythm without evidence of any arrhythmias. Atrial premature beats were recorded in 70 (80.5%) patients with a median of 6/day (interquartile range 3–20/day; maximum: 5180/day). Ventricular premature beats were recorded in 50 (57.5%) patients with a median of 4/day (interquartile range 2–19/day; maximum: 6847/day). Overall, seven patients (8%) had sustained atrial dysrhythmias: one had atrial fibrillation, one had atrial flutter, and five had atrial tachycardia. Sixty-six (75.9%) patients underwent TTE, which was mainly unremarkable as 65 patients had a normal left ventricular function, and three (4.5%) patients had evidence of pulmonary hypertension. Discussion: Cardiac arrhythmias are not uncommon among symptomatic COVID-19 recovered patients. Atrial arrhythmias were most common, with an up to 8% incidence rate. These findings may suggest that atrial dysrhythmias may be associated with long-term symptomatic sequela of COVID-19 infection. Funding Acknowledgement: Type of funding sources: None.